2019
DOI: 10.3390/brainsci9050104
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does the Prefrontal Cortex Play in the Processing of Negative and Positive Stimuli in Adolescent Depression?

Abstract: This perspective describes the contribution of the prefrontal cortex to the symptoms of depression in adolescents and specifically the processing of positive and negative information. We also discuss how the prefrontal cortex (PFC) activity and connectivity during tasks and at rest might be a biomarker for risk for depression onset in adolescents. We include some of our recent work examining not only the anticipation and consummation of positive and negative stimuli, but also effort to gain positive and avoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…This is in keeping with the meta-analysis and first quantitative review of emotional reactivity in depression that found consistent reductions in both positive and negative reactivity, which supported our previous study. 19,22 Interestingly, we did not find brain differences between the groups in the ventral striatum, which is consistent with our previous study examining young people at familial risk of depression but no personal depression experiences 20 nor did we find any relationship between anhedonia and the ventral striatum. This suggests that perhaps striatal differences (in this task) are only detectable after having experienced clinical depression and is thus a state rather than a trait marker of depression.…”
Section: Assessing Anticipation Effort and Consummationsupporting
confidence: 92%
“…This is in keeping with the meta-analysis and first quantitative review of emotional reactivity in depression that found consistent reductions in both positive and negative reactivity, which supported our previous study. 19,22 Interestingly, we did not find brain differences between the groups in the ventral striatum, which is consistent with our previous study examining young people at familial risk of depression but no personal depression experiences 20 nor did we find any relationship between anhedonia and the ventral striatum. This suggests that perhaps striatal differences (in this task) are only detectable after having experienced clinical depression and is thus a state rather than a trait marker of depression.…”
Section: Assessing Anticipation Effort and Consummationsupporting
confidence: 92%
“…Depression is associated with lower PFC activity, and reduced PFC function is a suggested risk factor for development of depression (Hare & Duman, 2020; Kaya & McCabe, 2019). Tobacco use is associated with altered nicotinic acetylcholine receptor availability in the PFC (Brody et al, 2016; Feduccia et al, 2012) which are integral to its function, especially in the dorsolateral PFC (DLPFC; Croxson et al, 2011; Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The prefrontal cortex is one of the most important cortical areas among the network of regions being involved in the pathogenesis of depression that plays a main role in the ability to process positive and negative emotions (Harms et al., 2017; Kaya & McCabe, 2019). Thus, the observed increase in levels of Fkbp5 in this brain area should not be surprising and may underlie a condition of potential increased vulnerability to stress.…”
Section: Discussionmentioning
confidence: 99%